Illicit Trade Prevention in Prophetic Hadith:: A Maqasid al-ShariÊ¿ah Perspective - Marwan Mas'ud; Hendri Waluyo Lensa; Nur Anisa Rizqi; Teguh Dwi Prayoga (El Nubuwwah Jurnal Studi Hadis, 2026)
The increasing prevalence of illicit trade poses significant challenges to economic justice, public security, and social stability. Although previous studies have predominantly examined illicit trade from legal, economic, and criminological perspectives, limited attention has been given to the normative framework of the Prophetic hadith and its relevance to contemporary social stability. This study aims to analyze the prevention of illicit trade from the perspectives of the Prophetic hadith, Critical Discourse Analysis (CDA), and Maqasid al-Shariah. Employing a qualitative library research design, the study applies thematic analysis to five relevant hadiths contained in al-Kutub al-Sittah and interprets them through the analytical frameworks of CDA and Maqasid al-Shariah. The findings demonstrate that the Prophetic hadiths establish a comprehensive ethical framework for preventing illicit trade by prohibiting fraud, unlawful commodities, hoarding, and transactions involving gharar, while promoting honesty and trustworthiness as the foundations of Islamic commercial ethics. These principles support the realization of the essential objectives of the Shariah, particularly the preservation of religion (hifz al-din), life (hifz al-nafs), wealth (hifz al-mal), and intellect (hifz al-aql), thereby strengthening public trust, market integrity, and social stability. This study concludes that the Prophetic hadith provides not only religious guidance but also a normative and ethical framework for contemporary policies aimed at preventing illicit trade and promoting sustainable economic governance. The study contributes to contemporary Islamic legal scholarship by integrating Prophetic hadith, Critical Discourse Analysis, and Maqasid al-Shariah into a unified analytical framework for illicit trade prevention.